THE INFLUENCE OF PARENTAL SUPERVISION ON CHILDREN'S ASSOCIATION IN SMA X - Michellia Michellia (Sean Institute, 2023)
Man cannot live alone. Likewise with children who attend High School X. They have to hang out to find their friends during school days. Not free from responsibility, parents must alpervise their children so that their association leads to the good not the bad. The author wants to research about parental supervision of children's associations. Do parents influence the association of a child. The formula technique that the author will use to respondents for this study is to use the Guttman Scale formula/technique. The Guttman scale technique provides only two answer choices, “yes” and “no”, so respondents' answers look more concrete. After being studied, it turns out that the influence of parental supervision greatly affects the way children get along at SMA X. The author has researched by distributing questionnaires to 30 children at SMA X who are suspected of having bad associations. After the author researched, it was proven that all the questions that the author spread were influential. Which means that it is true that parental supervision affects the way children get along. Children who lack parental attention cause their association to be bad. From parenting, communication, and learning patterns provided by parents. From this study, it can be concluded that parental supervision has an influence on children's associations. Parents have an important role in supervising and nurturing their children, so as not to fall into bad associations.